Nilai-nilai Psikosufistik dalam Aktivitas Keluarga Besar Ruqyah Aswaja Pusat Grobogan Purwodadi Jawa Tengah - Laila, Nur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Psychosufism actually as a psychological study of the understanding of Sufism which is defined as a science of human behavior whose concepts are built on the basis of the paradigm of Sufism which is based on the Qur'an and hadith. Psychosufism always prioritizes the development of inner potential towards psychological awareness to always be close to Him. Sufism and psychology have something in common, that is, both of them deal with psychological problems. Since the existence of Islam, Sufism has always focused on improving one's soul in order to achieve a more noble behavior and a peaceful life. Therefore, Sufism has the concept of psychological characteristics, such as khauf, mahabbah, ridha, remembrance, zuhud, and so on. This was also carried out by the Ruqyah Aswaja Family, Central Java, Grobogan Purwodadi. This study aims to determine the concept of ruqyah as psychosufistic and psychosufistic forms carried out by the ruqyah Aswaja extended family in Grobogan Purwodadi Central Java. This type of research is qualitative field research (field research) which seeks to gather information to obtain a complete understanding and analysis, which is supported by various sources in the form of books, papers and other research related to this research. By using the cultural anthropology method, researchers will focus on case studies by studying human interactions and ways of life in society.